Cognitive entry characteristics in mathematics and teaching effectiveness as correlates of students' achievement in quantitative chemistry in rivers state, Nigeria (2018)
Past studies have attributed poor performance of students to teachers ' and students' characteristics. However, no study seems to have related these characteristics to students' achievement in quantitative chemistry. This study therefore investigated the extent to which cognitive entry characteristics in mathematics and teaching effectiveness correlated with students' achievement in quantitative chemistry. The study adopted descriptive research design. Simple random sampling was used to select 3 local government areas (LGA) in Rivers State, 10 schools from each LG A and a Science class consisting of all chemistry students from each school. A total of 1652 students participated in the study. Instruments for data collection included: CEC in Mathematics Test, Students' Rating of TE and Quantitative Chemistry Achievement Test. Data was analysed using multiple regression. There was a positive and significant composite contribution of CEC in mathematics and TE to students’ achievement in quantitative chemistry (R= .27, R2 = .074, F(2, l649)= 66.310, p < 0.5). The CEC in mathematics contributed more (β = .262, t = 11.065, p< .05) than TE (β = . 066, t = 2.784, p < . 05). The study recommends that Chemistry students should be encouraged to improve on their CEC in mathematics needed to learn quantitative chemistry topics by revising their previous lessons. Chemistry teachers should be encouraged to attend seminars, conferences and workshops to improve on their teaching effectiveness